Cash flow projection for real estate development projects : a system dynamics approach - Liu, Chongming; Ogunlana, Stephen O.; Zhang, Shoutian; Nguyen L. Bach; The Government of Japan (Bangkok : Asian Institute of Technology, 1993)
Real estate development contributes much to the economic growth of a region or country. However, real estate development depends heavily on the economic trends. As such, it always appears dynamic in the development process. By employing system dynamics approach, a model is built up to include many factors affecting real estate development in order to gain insights of the development, particularly for development of condominium, one kind of residential high-rise buildings. The model is tested through testing the behaviors of sales management, construction man agement and financial management involved in the development. Optimization for different parameters and sensitivity analysis are conducted, and the results are also discussed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1993
Keywords: Real estate development